Epidemiological study of gastric Helicobacter spp. in dogs with gastrointestinal disease in Japan and diversity of Helicobacter heilmannii sensu stricto. (July 2017) - Kubota-Aizawa, Sanae; Ohno, Koichi; Fukushima, Kenjiro; Kanemoto, Hideyuki; Nakashima, Ko; Uchida, Kazuyuki; Chambers, James K.; Goto-Koshino, Yuko; Watanabe, Takayasu; Sekizaki, Tsutomu; Mimuro, Hitomi; Tsujimoto, Hajime
Highlights: Helicobacter heilmannii s.s. was the predominant gastric Helicobacter sp. in dogs with gastrointestinal diseases in Japan. H. heilmannii s.s. obtained in this study were diverse. H. heilmannii s.s. may be associated with moderate to severe gastritis in dogs in Japan. Helicobacter pylori infection was found in one case, representing the second report in a dog. A novel Helicobacter sp. may be present in canine stomachs in Japan. Abstract: Epidemiological and pathological studies of Helicobacter spp. in canine stomachs in Japan were performed to investigate strain specific pathogenicity. Gastric biopsies from 144 dogs with gastrointestinal diseases were evaluated for the presence of Helicobacter spp. using genus and species specific PCRs for Helicobacter felis, Helicobacter bizzozeronii, Helicobacter heilmannii sensu stricto (s.s.) and Helicobacter pylori . PCR indicated that 50/144 (34.7%) dogs were infected with Helicobacter spp. Of the genus positive samples, 21/50 could not be amplified by any of the species specific PCRs. To investigate Helicobacter at the species level, partial ureAB gene sequences from 48/50 genus positive samples were determined; 47 strains were identified. Thirty-five strains from 45 cases were closely related to H. heilmannii s.s. (89–99% sequence similarity), seven strains from seven cases were closely related to H. bizzozeronii (95–99% sequence similarity), three strains from three cases were closely related to Helicobacter felis (86%, 98% and 99% sequence similarity), one strain from one case was closely related to Helicobacter salomonis (99% sequence similarity) and one strain from one case was closely related to H. pylori (99% sequence similarity). Dogs infected with Helicobacter spp. most similar to H. heilmannii s.s. had a higher frequency of moderate to severe gastritis than dogs negative for Helicobacter spp. ( P = 0.044). In conclusion, the predominant Helicobacter spp. detected in canine stomachs in our study were most closely related to H. heilmannii s.s. and displayed substantial genetic diversity. Infection with Helicobacter spp. may be associated with more severe gastritis in dogs.